Sufficient Descent Conjugate Gradient Methods for Solving Convex Constrained Nonlinear Monotone Equations - San-Yang Liu; Yuan-Yuan Huang; Hong-Wei Jiao (Abstract and Applied Analysis)
Two unified frameworks of some sufficient descent conjugate gradient methods are considered. Combined with the hyperplane projection method of Solodov and Svaiter, they are extended to solve convex constrained nonlinear monotone equations. Their global convergence is proven under some mild conditions. Numerical results illustrate that these methods are efficient and can be applied to solve large-scale nonsmooth equations.